Analisis inhibitor korosi Alodine 1500 terhadap logam paduan aluminium 2219-T62 - Nugraha, Aditya Eka (Journal of New Energies and Manufacturing, 2022)
Aluminum alloy 2219 has good mechanical properties, but has lower corrosion resistance than other series aluminum alloys in humid environment. In this study, the corrosion rate of aluminum alloy 2219 was analyzed using the weight loss or immersion method in rain water which after being examined using litmus paper showed that rainwater in Tangerang City had a pH of 6. Simultaneously carried out an analysis of the efficiency of the use of alodine 1500 as an aluminum alloy 2219 inhibitor. The specimen used is aluminum alloy 2219 T62, cut to dimensions of 50 mm × 25 mm with a thickness of 1,8 mm and cleaned of dirt and corrosion that might exist using sandpaper and then cleaned using a chemical solution (pickling). Then the specimens were divided into two groups where one group was given alodine 1500 treatment, while the other groups was not given any inhibition treatment. After that, the two groups of specimens were immersed in a rainwater solution with variations of immersion for 336 hours, 504 hours, and 672 hours, then the corrosion rate was calculated and the efficiency of the use of alodine 1500 as an aluminum alloy 2219 inhibitor was also calculated. The morphology and chemical composition of the specimens were then investigated using Scanning Electron Microscopic – Energy Dispersive X-Ray (SEM-EDX)